Building a Framework for Sports Dispute Settlement: Legal Mechanism and Alternative Approaches in Indonesia - Silvana, Nina; Surono, Agus; Hamid , Adnan (Journal Evidence Of Law, 2025)
This study examines Indonesia’s sports dispute resolution landscape as well as the potential for building a comprehensive sports dispute settlement framework in Indonesia, analyzing current regulatory practices, arbitration processes, and alternative dispute resolution (ADR) mechanisms in the context of sports activities in Indonesia. This research will use doctrinal legal research methods and employs secondary data. Those data especially in the form of several legal materials, such as primary legal materials like acts or regulations as well as secondary legal materials like some studies conducted by several researchers previously. Data analyze will be undertaken qualitatively. By analyzing these issues, the paper outlines the necessary adjustments to Indonesia’s regulatory structure and the potential benefits of a dedicated sports dispute resolution body. It is important to harmonize arbitration processes with international standards to foster credibility especially after Indonesia has unified several arbitration institutions become only one institution, namely BAKI